2015
DOI: 10.1017/bca.2015.6
|View full text |Cite
|
Sign up to set email alerts
|

Cost Analysis of a School-Based Social and Emotional Learning and Literacy Intervention

Abstract: Purpose: There is limited research on the costs of social and emotional learning (SEL) interventions [Crowley, Jones, Greenberg, Feinberg & Spoth (2012). Resource Consumption of a Diffusion Model for Prevention Programs: The PROSPER Delivery System. Journal of Adolescent Health, 50 (3), 256–263]. This paper describes a comprehensive methodology for determining the costs of a successful universal, school-based SEL intervention that was implemented in nine public schools over 3 years.Methods: Resource costs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…This is a critical step change for the field, which has previously relied on estimates and simulations as opposed to direct measurement of QALYs. 22,128 Work to date has established a microcosting methodology for SEL interventions 129 and this has been applied to PATHS. 33 Building on this, our microcosting demonstrated that the mean incremental cost of the programme compared with usual provision was £29.93 per child.…”
Section: Longitudinal Relations Between Social Skills Mental Health mentioning
confidence: 99%
“…This is a critical step change for the field, which has previously relied on estimates and simulations as opposed to direct measurement of QALYs. 22,128 Work to date has established a microcosting methodology for SEL interventions 129 and this has been applied to PATHS. 33 Building on this, our microcosting demonstrated that the mean incremental cost of the programme compared with usual provision was £29.93 per child.…”
Section: Longitudinal Relations Between Social Skills Mental Health mentioning
confidence: 99%
“…These estimates are adapted from Long, Brown, Jones, Aber and Yates (2014, Tables 3 and 4). 16 The analysis by Long et al (2014) used the ingredients method and high-quality data to calculate a whole school costs analysis of 4Rs across grades.…”
Section: Rsmentioning
confidence: 99%
“…We estimate the incremental costs of introducing the 4Rs program into existing school activities. These estimates are adapted from Long, Brown, Jones, Aber and Yates (2014, Tables 3 and 4) 16 . The analysis by Long et al.…”
Section: Benefit-cost Analysis Of Sel Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three of the six papers in this volume address SEL or noncognitive outcomes in some manner (Belfield et al, 2015;Jones et al, 2015;Long et al, 2015), a testament to the growing recognition that these outcomes are important predictors of positive development. Whereas Long and colleagues focus on the cost of an SEL intervention, Jones et al (2015) and Belfield et al (2015) directly tackle the need to expand benefits models to directly incorporate noncognitive outcomes.…”
Section: Expanding the Frontiers Of Benefit-cost Analysis Of Preventimentioning
confidence: 99%